2021
DOI: 10.1108/jsbed-12-2020-0443
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five years of the Journal of Small Business and Enterprise Development: a bibliometric review

Abstract: PurposeCommensurate with the 25th anniversary of the Journal of Small Business and Enterprise Development (JSBED), this retrospective work distils trends across all original articles published in the journal during this time period.Design/methodology/approachBibliometric analysis techniques are used to analyse 917 original JSBED publications. Specifically, performance analysis is conducted to analyse the journal's publication and citation patterns, bibliographic coupling and author keyword co-occurrence analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 118 publications
0
16
0
Order By: Relevance
“…As a key source of entrepreneurship, family businesses are seen as a source of economic development and growth (Lwango et al. , 2017; Kumar et al. , 2021).…”
Section: Analysis Of Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a key source of entrepreneurship, family businesses are seen as a source of economic development and growth (Lwango et al. , 2017; Kumar et al. , 2021).…”
Section: Analysis Of Conceptsmentioning
confidence: 99%
“…Previous researchers conducted literature reviews to examine different disciplines in the scientific area of family businesses, such as family business goals and organizational culture behavior (Vallejo-Martos, 2011;Gupta and Levenburg, 2012;Vallejo, 2016;Alaya et al, 2017;Litzky et al, 2020), familiness and business strategy (Basco, 2015;Basly, 2017;Kumar et al, 2021), family business structure (Pucci et al, 2017;Fathallah et al, 2020;Herrera and de las Heras Rosas, 2020), conflicts in family businesses (Soleimanof et al, 2018;Razzak et al, 2021), family entrepreneurship and culture (Leal-Rodr ıguez et al, 2017;Randerson et al, 2020), and the innovation process in family businesses (Roffia et al, 2021;Alves et al, 2020).…”
Section: Previous Literature Reviews On Family Businessesmentioning
confidence: 99%
See 1 more Smart Citation
“…The data for bibliometric analysis can be sourced from various databases and aggregators like Google Scholar, WoS, SciELO and Scopus (Archambault et al, 2009). The Scopus database has been extensively used for conducting bibliometric studies (Baker et al, 2020a;Sureka et al, 2021;Kumar et al, 2021). The emergence of Scopus as a preferred source is driven by the comprehensive coverage of Scopus, with more than 75 million documents and nearly 25,000 sources (Scopus, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Diversity is increasingly becoming a significant and exciting research area for the satisfactory performance of small family businesses, especially in multicultural markets like the US, which boast many diverse segments of entrepreneurs. Past research found a growing interest in research on prevalent entrepreneurial orientation and entrepreneurship themes in underrepresented and minority populations (Kumar et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%